2016
DOI: 10.1097/mbc.0000000000000372
|View full text |Cite
|
Sign up to set email alerts
|

Novel hematologic inflammatory parameters to predict acute mesenteric ischemia

Abstract: Acute mesenteric ischaemia (AMI) is an emergency condition that requires urgent diagnosis. Neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) have been studied as inflammatory biomarkers in atherosclerosis, but data regarding AMI are lacking. The study population included patients with AMI (n = 46) versus age and sex-matched healthy controls (n = 46). Computed multidetector tomographic angiography was performed to diagnose AMI. NLR and PLR were calculated using complete blood count. C-reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 24 publications
1
21
1
1
Order By: Relevance
“…[20] Studies of P/L ratio, however, are limited in the literature. A study conducted by Toptas et al [10] reported that elevated P/L ratio, along with elevated levels of other hematological markers, would be an important marker in the diagnosis of AMI, as well as prediction of prognosis and mortality. Our study results included a statistically significant difference in survival according to P/L ratio.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[20] Studies of P/L ratio, however, are limited in the literature. A study conducted by Toptas et al [10] reported that elevated P/L ratio, along with elevated levels of other hematological markers, would be an important marker in the diagnosis of AMI, as well as prediction of prognosis and mortality. Our study results included a statistically significant difference in survival according to P/L ratio.…”
Section: Discussionmentioning
confidence: 99%
“…P/L ratio has been studied in many inflammatory events, ranging from coronary artery disease to malignancies, and its value in prediction of prognosis has been well demonstrated. [9,10] A study conducted by Kahramanca et al [17] reported that P/L ratio was a good marker to estimate prognosis and debridement of Fournier's gangrene. It has also been shown to be an important marker for malignancy, and a study conducted by Stotz et al [18] reported that elevated P/L value was a negative factor regarding curative resection in gastrointestinal stromal tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Холестероловые кристаллы, эмболизируя артериолы, повреждают эндотелий, индуцируя активацию свёртывающей системы крови с агрегацией тромбоцитов, что приводит к микротромбообразованию, ишемии и некрозу ткани, тромбоцитопении потребления. По мнению ряда авторов, развитие тромбоцитопении и системной воспалительной реакции после операции на брюшной аорте является маркером абдоминальной катастрофы, в том числе и при ОННМК [8,14,15].…”
unclassified